2009
DOI: 10.1097/aci.0b013e32832b1f00
|View full text |Cite
|
Sign up to set email alerts
|

Egg allergy in childhood: an update

Abstract: Egg allergy generally has a good prognosis. Despite recent advances in oral immunotherapy trials, the treatment of egg allergy currently relies on avoidance of egg-containing foods until tolerance has developed. It remains unclear whether the ongoing low-dose exposure to egg proteins in cooked foods improves the natural history of egg allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 98 publications
0
25
0
1
Order By: Relevance
“…Egg contains 5 major allergens: ovomucoid (28 kDa), ovalbumin (43 kDa), ovotransferrin (78 kDa), lysozyme (14 kDa), and chicken serum albumin (69 kDa), which is the only major allergen present in the yolk [118]. Ovomucoid is considered the immune dominant protein and is noted by its stability to thermal conditions [7].…”
Section: Eggmentioning
confidence: 99%
“…Egg contains 5 major allergens: ovomucoid (28 kDa), ovalbumin (43 kDa), ovotransferrin (78 kDa), lysozyme (14 kDa), and chicken serum albumin (69 kDa), which is the only major allergen present in the yolk [118]. Ovomucoid is considered the immune dominant protein and is noted by its stability to thermal conditions [7].…”
Section: Eggmentioning
confidence: 99%
“…[22] Previous studies have demonstrated a good prognosis for egg allergy, with around 50% of egg allergic children outgrowing the condition by the age of 3 years, and 66% by the age of 5 years. [44,45] Factors associated with persistence of egg allergy include:…”
Section: Eggmentioning
confidence: 99%
“…About two-thirds of children will outgrow their egg allergy by early school age (1). The persistence of egg allergy or its late onset has usually a less favourable prognosis.…”
Section: To the Editormentioning
confidence: 99%
“…Alpha-livetin or chicken serum albumin (Gal d 5) is the major allergen in egg yolk, being implicated in the bird-egg syndrome. 1 Food tolerance mechanisms are not completely understood but there are several known factors that can affect it. 2 It is postulated that a failure in oral tolerance induction or a breakdown in previously acquired tolerance results in food hypersensitivity.…”
Section: To the Editormentioning
confidence: 99%